Republic of Moldova : First Reviews Under the Extended Credit Facility and Extended Fund Facility Arrangements and Request for Modification of Performance Criteria-Press Release; and Staff Report. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2017)
This paper discusses Moldova's First Reviews under the Extended Credit Facility and Extended Fund Facility Arrangements and Request for Modification of Performance Criteria. The program is broadly on track, enjoys strong country ownership, and is supported by policymakers' firm commitment to sound economic management. The authorities continue to make significant progress in tackling long-standing vulnerabilities in the financial sector and advancing structural reforms. These efforts have helped strengthen financial stability, and growth has resumed. The economy is projected to grow 4.5 percent in 2017, higher than previously expected. Continued steadfast program implementation is vital.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet